Ichthyosis hystrix disease or verrucous epidermal nevus (a retrospective analysis of 20-year observation) - V. D. El'kin; T. G. Sedova; E. V. Plotnikova; I. D. Kuznetsov; M. Yu. Novoselova (Alʹmanah Kliničeskoj Mediciny, 2017)
We present a  clinical case of ichthyosis hystrix, a rare genetic ichthyosiform dermatosis. Specifics of the disease are related to the complexity of differential diagnosis and verification of the diagnosis, because clinical manifestation of ichthyosis hystrix is similar with that of verrucous epidermal nevus. Clinical particulars of both nosologies are characterized by bizarre and widespread skin lesions of spicular hyperkeratotic growth, located along Blaschko lines. The exclusive feature of the clinical case described is a  long-term (20 years) clinical and laboratory monitoring of the patient. The literature review provides brief information on etiology, pathogenesis, clinical features, differential diagnosis, and pathomorphology of ichthyosis hystrix and verrucous epidermal nevus.